2018
DOI: 10.22201/fca.24488410e.2018.1488
|View full text |Cite
|
Sign up to set email alerts
|

Modelos centrados vs descentrados para la predicción de quiebra: evidencia empírica para España

Abstract: <p>Usando información financiera de empresas españolas pertenecientes a distintos sectores económicos, este estudio ha desarrollado modelos centrados y descentrados para la predicción de quiebra. La comparación de ambos tipos de modelos nos ha permitido determinar la superioridad de los modelos descentrados, que en la mayor parte de los casos muestran una gran capacidad de predicción y un fuerte ahorro de costes de elaboración frente al desarrollo de numerosos modelos centrados. Este estudio también apor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Such is the case of the model proposed by Gu and Gao (2000) with hotels and restaurants, that of Kim and Gu (2006b) for hotels, restaurants, and casinos, and that of Park and Hancer (2012) with a sample of hotels, restaurants and, entertainment service companies. Also, the usefulness and greater precision of global bankruptcy prediction models have already been shown in general in the studies by Alaminos, del Castillo and Fernández (2016) and Laguillo et al (2019).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Such is the case of the model proposed by Gu and Gao (2000) with hotels and restaurants, that of Kim and Gu (2006b) for hotels, restaurants, and casinos, and that of Park and Hancer (2012) with a sample of hotels, restaurants and, entertainment service companies. Also, the usefulness and greater precision of global bankruptcy prediction models have already been shown in general in the studies by Alaminos, del Castillo and Fernández (2016) and Laguillo et al (2019).…”
Section: Discussionmentioning
confidence: 80%
“…Alaminos, del Castillo and Fernández (2016) developed a global model with samples of Asian, European, and American companies and concluded that its precision was higher than that of the models focused on each region with information of up to three years before the bankruptcy. Recently, Laguillo et al (2019) used a sample of Spanish companies from different industries and found that the global model built surpassed the models focused on each industry.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As another aim is to keep works that provide clear-cut hotel results, studies using broader tourism or hospitality firm samples inseparably and in an indistinguishable manner are not included (Abidin et al 2020(Abidin et al , 2021Barreda et al 2017;Laguillo et al 2019;Li et al 2017Li et al , 2019Park and Hancer 2012;Pisula 2020). Another sub-filter regarding study relevance is the exclusion of ex ante bankruptcy risk assessments that do not deal with actual bankruptcies or a measure of financial distress, where the aim is to project a future potential credit profile for hotels (Gallo et al 2018;Matejić et al 2022;Špiler et al 2022;Vivel-Búa et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This fact can prohibit generating low p-values (Kalnins 2016), although with increasing data quality and the ability of methods to handle small numbers of default events (e.g., Ho et al (2013) use 12 default events and Sandin and Porporato (2008) use 11), these issues are gradually surpassed. On the other hand, del Castillo García and Fernández Miguélez (2021) and Laguillo et al (2019) question sector-specific models, as a sectoral approach can increase the costs of development and further maintenance and may not increase the accuracy significantly.…”
Section: Firm Failures In the Hotel Industry: Motivation For Sectoral...mentioning
confidence: 99%